X-ray and optical emission from large superbubbles including the stellar photoionization. Issue 3 (2nd February 2022) - Schneiter, E M; Reyes-Iturbide, J; Velázquez, P F; Esquivel, A
ABSTRACT: N70 is a giant superbubble (SB) produced by the stellar cluster LH 114. The dynamic of the stellar SB can be explained with hydrodynamic simulations. However, the explanation of the observed X-ray luminosity is still a matter of debate. Observations show that this kind of superbubbles exhibits X-ray luminosities of the order of 10 35 erg s −1, which cannot be explained by only considering the mechanical luminosity of the stellar components. Instead, theoretical models predict luminosities one order of magnitude lower. In this work, we attempt to answer this discrepancy by including a core-collapse supernova explosion (SN) and the photons emitted by each of the stars involved. We find that a core-collapse SN, with an initial mass of 10 M⊙, can explain the missing X-ray emission, lasting approximately 1000 yr. Also, the radiation produces an enhancement of the filamentary superbubble morphology and it increases the SB radius by 23 per cent with respect to the pure hydrodynamic case.